(untitled) (LEARNing Landscapes, 2015)
As the practitioner-researcher, the author integrated social and participatory media into her classes. Action research was used to explore how such media might enhance learning. The study found that the unique qualities of new media could be used to develop an active environment; students learned a lot from each other. Many complexities and tensions emerged and a shift in the teacher-to-student relationship occurred resulting in the need for the author to unlearn many past teaching practices.